A MODEL FOR IMPLEMENTING MONETARY AND BANKING POLICIES : (CASE STUDY IN IRAN) - baharloo, Aliaskar; Sharifzadeh, Fatah; Rabiei, Mahnaz; Hosseini Golafshani, Seyed Ahmad (Gênero & Direito, 2020)
This research has addressed the pathology of the implementation of monetary and banking policies in Iran and identifying the factors affecting the implementation of these policies in the banking system. In this research, concurrent with collecting researches and studies performed about the factors affecting the implementation of policies, by conducting exploratory interviews with 20 experts in the field of policy-making and banking and monetary experts, 36 indicators affecting the implementation of monetary and banking policies in Iran were also identified. Afterwards, in order to fit the "proposed analytical model of implementing monetary and banking policies in Iran", 13 hypotheses were defined. Then, by selecting appropriate statistical sample and distributing the questionnaire among them, the fitness of the model was investigated. Finally, the proposed research model for implementing monetary and banking policies in Iran was fitted and confirmed, and out of 13 hypotheses, 2 were rejected and the rest were confirmed.